Preferensi Metodologi Pembelajaran Bahasa Arab Mahasiswa PBA UIN Saifuddin Zuhri Purwokerto di Era Pasca Pandemi - Muhammad Sya'dullah Fauzi; Fatahillah, Mubarok; Muhammad Miftah Faridl (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to determine the preferences or tendencies of Arabic learning methodologies for PBA students at UIN Saifuddin Zuhri Purwokerto in the post-pandemic period. This research is a qualitative type of research that seeks to explore a person's experience and then identify experiences, points of view, frame of mind, and opinions in depth about a real-life phenomenon. Meanwhile, the data collection technique used semi-structured interview and then analyzed using thematic analysis method. The results of this study revealed that the majority of PBA students at UIN Saifuddin Zuhri considered that blended learning was actually effective for learning Arabic in the post-pandemic period. however, with all its advantages and disadvantages, they tend to expect Arabic learning to be carried out face-to-face in full while still utilizing the role of technology. Because after all, technology can help a lot for the process of learning Arabic for students. In addition, 70% of students tend to choose the Arabic language learning method with the tarjamah grammatical method using a cooperative learning model. While the rest tend to choose the direct method by actively interacting between lecturers and students, where the lecturer plays a role in providing stimulus in the form of examples, while students only respond in the form of imitation, answering questions and demonstrating. For this reason, the Arabic language learning methodology in the post-pandemic period must be adapted to the circumstances and tendencies of students while still utilizing the role of technology.